Qualitative research into motivations and barriers to cycling in UMP campus - Nadiah, Hudoh @ Ramli (2016)
Nowadays, global warming has become one of the main concerns of our world. The role of transportation is significant as it emits 15% of the total emission of Carbon Dioxide (CO2). As an environmental friendly, cycling is considered as an alternative for cars and other motorized vehicles, especially for short journeys .This study has revealed the barriers and motivations to cycling among UMP community. A total of 120 respondents was selected for this survey, represented the male and female. Review of literature was conducted and a questionnaire survey was used to obtain the information needed to meet the requirements of this inquiry. The reasons provided as barriers to cycling are safety issues, health / ability to ride issues, time issues, and weather issues. After gathering the data, a descriptive analysis was performed with the help of SPSS (version 17) in getting cross tabulation data and finding ‘mean’ values for each questions. From the results, four main barriers were identified as the main findings, which were: drivers not educated in safety for cyclist / unaware of cyclist, lazy/tired / no motivation, takes more time than alternative commutes and the weather is extreme hot. For the motivators, two ways were identified. One is to organize an interesting cycling activities and another one is to provide a bicycle lane. The mean value for the motivators is higher than barriers which is 4.38. Based on these findings, some solutions were proposed to improve the attitude, solve the obstacles, and meet the demands to promote cycling in UMP Gambang Campus so that a high level of sustainability can be achieved.